2007
DOI: 10.1111/j.1468-3148.2006.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Physical, Intellectual and Social Impairments on Survival in Adults with Intellectual Disability: A Population‐Based Register Study

Abstract: Background Research into factors associated with survival in adults with intellectual disability is limited and no studies have controlled for changes in these factors over time.Material and Methods All adults aged ‡20 years with moderate to profound intellectual disability (approximate IQ < 50) using specialist services in Leicestershire and Rutland, UK, were identified. The relationship between survival and physical, intellectual and social impairments was investigated, also adjusting for age, sex, ethnicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…However, these studies should not be considered to be independent. In addition, there were two publications that used data collected from 1987 onwards from the Leicestershire learning disabilities register (McGrother et al 1996;Tyrer et al 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies should not be considered to be independent. In addition, there were two publications that used data collected from 1987 onwards from the Leicestershire learning disabilities register (McGrother et al 1996;Tyrer et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…From the methods reported, it appeared that many of the participants from the second study were also analysed in the first one. Whereas Tyrer et al (2007) report on a larger sample using a clearer definition of mobility impairment, McGrother et al (1996) offer different comparison groups for mobility prevalence and a perspective of the effect using a different definition upon the prevalence of mobility limitations. Both of these publications are presented in the results, but again it must be recognised that they are not completely independent.…”
Section: Resultsmentioning
confidence: 99%
“…Had those with mild ID been included in the numerator for this study, the reported SMRs are likely to have been lower, because the risk of premature death is greater in people at the more severe end of the ID spectrum (Patja et al. 2001; Tyrer et al. 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…We have found that those with mild ID who are enrolled on the register often have significant adaptive and challenging behaviour problems that cannot be managed effectively by mainstream services and thus are referred for specialist care. Had those with mild ID been included in the numerator for this study, the reported SMRs are likely to have been lower, because the risk of premature death is greater in people at the more severe end of the ID spectrum (Patja et al 2001;Tyrer et al 2007b). Another point for consideration is that adults only were investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence reported is considered an administrative prevalence of intellectual and developmental disabilities, as only individuals receiving support from social, health, voluntary, or independent sector services are included. The identification of the entire population of persons with intellectual and developmental disabilities is not possible (Bhaumik, Tyrer, McGrother, & Ganghadaran, 2008); however, the register is estimated to capture 95% of individuals with moderate to profound disabilities (Tyrer, Smith, McGrother, & Taub, 2007).…”
Section: Leicestershirementioning
confidence: 99%